Parametric Study On The Production Of Dried Long Fiber In Palm Oil Mill - Laupe, Laudin (Universiti Sains Malaysia, 2017)
This case study was carried out at Kilang Minyak Sawit Kamunting Sdn. Bhd, Taiping aiming in increasing the production of dried palm oil fiber. This could be achive by improving the speed of the drum and suitable temperature as an input for the machine. Dryer drum is one part of dried long fiber machine that function as sieving and drying the shredded palm oil fiber. At the end of the dryer drum there were only long fiber palm oil in abundance then being transferred to packing machine to be pack. The scope of the study is to investigate the suitable speed and temperature input by using parametric study on it. Speed and temperature are playing the important rule to make sure the production and quality of the palm oil fiber is follow the company requirement. It shows that the time taken of the production is constant certain speed and the higher temperature input will decrease the moisture content. In addition, experimental on palm oil fiber mechanical properties also being carried out with and without alkaline treatment. Single Fiber Tensile testing was done to see the effect on treatment with three different concentration NaOH. The experiment indicates that the palm oil fiber with treatment shows better mechanical properties than the untreated. Microstructural observation also was done using SEM to see the physical effect by the treatment to support the effect of the tensile testing.